Does compaction degree and particle size influence bromatological composition and mycotoxin levels in corn silage? - Toledo, Eduardo Amaral; Pertile, Simone Fernanda Nedel; Sifuentes dos Santos, Joice; Barreto, José Victor Pronievicz; Banchero, Georgete; dos Santos, Marcelo Diniz; Venâncio, Rafael Luiz; Ribeiro, Edson Luiz Azambuja; Zamboti, Mateus; Zundt, Marilice; et al. (Scientia Plena, 2020)
The objective of this study was to evaluate the effects of compaction degree and particle size on the presence of mycotoxins and the bromatological composition of corn silages. Samples from 47 silos with forage corn silage were collected from the northern region of Paraná State, Brazil. The bromatological composition and concentration of mycotoxin in silages were analyzed according to both the compaction degree (600 kg.m-3 and 700 kg.m-3) and particle size. Mycotoxins were detected using enzyme-linked immunosorbent assay, and test results were considered positive when the mycotoxin concentration was above the detection limit of 100 µg.kg-1 for deoxynivalenol, 2.5 µg.kg-1 for aflatoxin, 5 µg.kg-1 for zearalenone, and 200 µg.kg-1 for fumonisin. Silages with 600 kg.m-3 compaction degree had higher initial and final pH than silages with a higher compaction degree. Silage with a mean particle size less than or equal to 14.56 mm had 12% higher dry matter content than silage with a mean particle size more than 14.56 mm. There was no effect of the compaction degree or particle size on the concentration of mycotoxin, and 83% of the analyzed samples had contamination above the detection limits according to at least one of the studied mycotoxins. Silages with smaller average particle sizes had higher dry matter content. Thus, the degree of compaction and particle size did not affect the presence of mycotoxins in corn silage